Body/Language: Embodied Sexuality in Cyberspace and Spike Jonze’s Her - McGrath, Meadhbh (Graduate Students’ Union of the University of Dublin, Trinity College, 2015)
This essay offers a sustained analysis of the role of embodiment in cybersex, with reference to “phone sex” in Spike Jonze’s Her (2013) and chat-based “tinysexual” encounters online (particularly those which are described in Julian Dibbell’s My Tiny Life (1999)). I argue that cybersex neither suppresses the body nor expresses a “postcorporeal” sexuality separate from the body, but instead demands a new way of conceiving and perceiving the relationship between desire, fulfilment and the body. I propose that cybersex fundamentally involves the performance of a body, and that this virtual body emerges from a process of interaction with other users. I examine how language provides a means of embodiment to cybersex participants, and how cybersex can be considered as a writing exercise or text fantasy, in which writing skills are invaluable. My argument is based on Allucquére Rosanne Stone’s conception of cybersex as data compression, where a single mode of communication carries not just words but the representation and performance of a body. The paper also explores how cyberspaces offer users a greater degree of fluidity in self-presentation, yet users still choose to construct their virtual bodies more rigidly in accordance with the prevailing images of beauty in the “real world.” Finally, I consider the untapped potential for exploration of queerness and non-normative sexualities in cyberspace. The paper concludes that at the same time as cybersex transcends boundaries, it is deeply heteronormative and conservative, as users continue to impose limits on their virtual bodies
Keywords: embodiment; LambdaMOO; Spike Jonze; cyberspace; cybersex